2004
DOI: 10.1145/1035134.1035136
|View full text |Cite
|
Sign up to set email alerts
|

The obstacles and myths of usability and software engineering

Abstract: Avoiding the usability pitfalls involved in managing the software development life cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
107
1
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(116 citation statements)
references
References 4 publications
0
107
1
8
Order By: Relevance
“…Aikio [3] indicated that usability methods are unknown, underused, and inaccessible to common developers and small-and medium-sized software-development teams. However, in order to consider usability in software-development teams, there are four ways to do so, which are listed below [8]:…”
Section: Usability and Small Software Development Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aikio [3] indicated that usability methods are unknown, underused, and inaccessible to common developers and small-and medium-sized software-development teams. However, in order to consider usability in software-development teams, there are four ways to do so, which are listed below [8]:…”
Section: Usability and Small Software Development Organizationsmentioning
confidence: 99%
“…In addition, usually small-sized software organizations develop small-sized projects. For such projects, software-development teams can usually avoid the direct involvement of usability experts or practitioners due to the availability of methods that can be applied by non-usability experts such as developers on development teams [8]. Furthermore, small organizations utilize resources (employee) efficiently.…”
Section: Usability and Small Software Development Organizationsmentioning
confidence: 99%
“…Studies have shown that user-centred design techniques are still underused among development teams [12] and most usability issues are only detected during testing and after deployment [13,14]. Of those practicing UCD, one investigation revealed that the majority of methods in practice were informal, low-cost user-centered design methods.…”
Section: Usability and Web Development Processesmentioning
confidence: 99%
“…Nielsen gave one of the most well-known descriptions related to software system learnability and memorability, efficiency of use, ability to avoid and manage user errors, and user satisfaction (Nielsen, 1993). In spite of the relevance of usability in software development it is still insufficient in most software systems (Seffah, 2004) (Bias, 2005).…”
Section: Introductionmentioning
confidence: 99%